1971
DOI: 10.1051/jphyscol:19711104
|View full text |Cite
|
Sign up to set email alerts
|

Neutron Scattering Studies of Some Spinels

Abstract: The magnetic structures of a number of single and mixed spinel ferrites have been determined using the polarised neutron diffraction technique. It is shown that this method is applicable even when the structure is noncollinear. The experimental magnetization curves in MgFe2O4 have been fitted to a molecular field expression to derive the dominant exchange interactions as JAB = — 22 °K and JAA = — 4 °K. From paramagnetic neutron Scattering, the only dominant exchange interactions in ZnFe2O4 and ZnCr2O4 have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Other authors found a very low degree of inversion. [118,119] Faller and Birchenall [120] showed that in some cases even rapid quenching is not sufficient to retain the equilibrium distribution of cations corresponding to the annealing temperature. Therefore, the experimental data on the degree of inversion (fraction of Mn ions in octahedral sites) from Jirák and Vratislav was used to evaluate the cation distribution in MnFe 2 O 4 .…”
Section: Fe-mn-omentioning
confidence: 98%
“…Other authors found a very low degree of inversion. [118,119] Faller and Birchenall [120] showed that in some cases even rapid quenching is not sufficient to retain the equilibrium distribution of cations corresponding to the annealing temperature. Therefore, the experimental data on the degree of inversion (fraction of Mn ions in octahedral sites) from Jirák and Vratislav was used to evaluate the cation distribution in MnFe 2 O 4 .…”
Section: Fe-mn-omentioning
confidence: 98%
“…The metaferrite films were deposited onto a GaAs substrate (devices using these films can be monolithically integrated with GaAs circuits [3], [4]). The S -parameters determined with the HFSS 13.0 were used to calculate the quantities of interest.…”
Section: Results For the Metaferrite Parametersmentioning
confidence: 99%
“…Average size of the film nanograins is of 4 -20 nm [8], [10] (no grater than the film thickness when it is the case). Each nanocrystal has a tetragonal ferrite structure, with a 0 = b 0 = 8.389 Å, c 0 = 8.488 Å [3]. The structure is of spinels (figure 1) and presents the exchange interactions between Fe 3+ -Fe 3+ ions.…”
Section: Structural Detailsmentioning
confidence: 99%